1986
DOI: 10.1038/clpt.1986.174
|View full text |Cite
|
Sign up to set email alerts
|

The effects of single-dose atenolol, labetalol, and propranolol on cardiac and vascular function

Abstract: The pharmacodynamic effects of single oral doses of atenolol (100 mg), labetalol (300 mg), and propranolol (80 mg) were compared with those of placebo in a randomized, double-blind, Latin square design in 12 patients with hypertension. Atenolol and propranolol both significantly reduced cardiac output (-0.55 vs. -0.31 L/min) and heart rate (-8.0 vs. -6.6 bpm), whereas labetalol had no effect on either parameter (-0.08 L/min; + 1.0 bpm). Labetalol significantly reduced vascular resistance (-339 dynes X cm/sec5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In contrast, an intravenous infusion of atenolol caused no fall in arterial pressure at 15 minutes and significant falls only after 1 to 3 hours in the case of the diastolic pressure [13]. Similar differences have been found between oral labetalol and atenolol by Holtzman et al [14], who showed that the major mechanism of labetalol's hypotensive effect was by acute vasodilation. In severely hypertensive subjects, labetalol (100 to 125 mg intravenous bolus) was compared with propranolol (10 mg intravenous bolus); within 5 minutes labetalol had had a hypotensive effect which was sustained for 3 hours, whereas propranolol did not decrease the pressure at all [15].…”
Section: Labetalol: Acute Vasodilatory Effects On Blood Pressure In Hsupporting
confidence: 68%
“…In contrast, an intravenous infusion of atenolol caused no fall in arterial pressure at 15 minutes and significant falls only after 1 to 3 hours in the case of the diastolic pressure [13]. Similar differences have been found between oral labetalol and atenolol by Holtzman et al [14], who showed that the major mechanism of labetalol's hypotensive effect was by acute vasodilation. In severely hypertensive subjects, labetalol (100 to 125 mg intravenous bolus) was compared with propranolol (10 mg intravenous bolus); within 5 minutes labetalol had had a hypotensive effect which was sustained for 3 hours, whereas propranolol did not decrease the pressure at all [15].…”
Section: Labetalol: Acute Vasodilatory Effects On Blood Pressure In Hsupporting
confidence: 68%